Effectiveness of Nurse led education on Knowledge regarding post operative care among total knee-replacement surgery patients in selected hospitals at Trichy - Ms.D. Selvarani; Dr. M. Gandhimathi; Dr. Suja Suresh (The Bioscan, 2025)
Aims and objectives To determine the effects of Nurse led education on postoperative care among total knee-replacement patients. Background Most total knee-replacement patients experience pain and limited physical activities during recovery and rehabilitation. Many patients fail to implement an effective rehabilitation plan because of the pain and a lack of practical knowledge regarding the rehabilitation process. Design Quasi-experimental design. Methods We recruited 30 total knee-replacement patients for our study. The experimental group (n = 15) received a health-educational intervention. The control group (n = 15) received routine care. Results The experimental group reported lower levels of postoperative pain than the control group. The stair-climbing ability of the experimental group was superior to that of the control group. The experimental group also had superior scores for regular straight-leg raises and muscle power of the affected leg, compared with the control group. Conclusion The preoperative health-educational intervention reduced the level of postoperative pain experience by total knee-replacement patients, increased the regularity with which they performed rehabilitative exercises and accelerated the recovery of their physical functioning. Relevance to clinical practice The health-educational model can be included in regular clinical management and care of total knee-replacement patients.